Feasibility of Use of the Clinical Internship Evaluation Tool in Full-Time Clinical Education Experiences: A Multi-institutional Study. Issue 3 (23rd September 2022) - Birkmeier, Marisa; Wheeler, Emma; McGregor Garske, Heidi; Gorman, Sharon Lynn; Richards, Heather; Wolff-Burke, Melissa; Bureau, Megan R.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: The Clinical Internship Evaluation Tool (CIET) is a reliable and valid clinical education assessment tool but is used less frequently by physical therapist education programs than the Physical Therapist Clinical Performance Instrument (PT CPI). The purposes of this exploratory study were to: 1) explore CI and student perceptions for the CIET as an accurate and user-friendly measurement of physical therapist (PT) student clinical performance; and 2) to compare stakeholder perceptions of CIET as a clinical performance tool to PT CPI. Methods: Clinical instructors and PT students were recruited from 5 geographically diverse physical therapist education programs and completed both the PT CPI and CIET at the midterm and final evaluation during a full-time clinical education experience. A post-survey collected data related to participants' perceptions of tool feasibility and ease of use. The Wilcoxon sign rank test was used to determine whether significant differences existed in the participants' perceptions related to the utility of the CIET versus PT CPI. Results: One hundred one participants (56 PT students; 45 CIs) completed the study. Most student and CI participants (91.1%) indicated that the CIET completion time was < 45 minutes. More students (66.1%) and CIs (73.3%) reported a PT CPI completion time of > 45 minutes. Students (71.4%) and CIs (68%) preferred the CIET to the CPI. There was a significant difference in perception of ease of use (Z-score = −5.42, P < .001), appropriate completion time (Z-score = −7.25, P < .001), and little redundancy of items (Z-score = −7.17, P < .001). Discussion and Conclusion: Students and CIs preferred the CIET which was perceived to be easy to use and completed in < 45 minutes while still retaining the ability to accurately measure student performance in clinic. Clinical education requires efficient, valid, and reliable assessment tools to match the dynamic needs of a changing health care environment.